2019
DOI: 10.1002/pon.5267
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of internet‐delivered cognitive behaviour therapy for clinical depression and/or anxiety in cancer survivors (iCanADAPT Early)

Abstract: Purpose: To evaluate internet-delivered cognitive behavioural therapy (iCBT) on clinical depression and/or anxiety, distress, fear of cancer recurrence, and quality of life in cancer survivors. Methods: Random assignation of 114 participants to iCBT or treatment-as-usual (TAU). The clinician-supervised iCBT program (iCanADAPT Early) consisted of eight lessons over 16 weeks. Self-report questionnaires occurred at baseline, midpoint, and posttreatment for both groups with 3-month follow-up for iCBT participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 30 publications
4
70
0
3
Order By: Relevance
“…32 Thus, it seems important to adjust the program to the user's life situation. A recent RCT investigating iCBT in individuals with cancer 35 included fewer, predetermined modules over a longer period of time (16 weeks) and showed positive results for both anxiety and depression at an early follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…32 Thus, it seems important to adjust the program to the user's life situation. A recent RCT investigating iCBT in individuals with cancer 35 included fewer, predetermined modules over a longer period of time (16 weeks) and showed positive results for both anxiety and depression at an early follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increase in research into online interventions addressing the psychological aspects of cancer survivorship has occurred. By 2020, a systematic review identified 33 publications relating to internet interventions for cancer-related distress ( Willems et al, 2020 ), and another 2019 systematic review identified four such interventions addressing the fear of cancer recurrence ( Tauber et al, 2019 ) with further randomized controlled trials (RCTs) into insomnia ( Zachariae et al, 2018 ) and clinical depression and/or anxiety in cancer survivors ( Murphy et al, 2020 ). The explosion of research into online interventions relating to cancer survivorship is not mirrored for those living with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these recent trials targeted a single disorder, whereas our intervention adopts a transdiagnostic approach targeting both depression and anxiety simultaneously ( Clark, 2009 ). Transdiagnostic CBT uses “ universally applied therapeutic principles, empirically based modular strategies, and targeting shared mechanisms across classes of disorders ” ( Sauer-Zavala et al, 2017 ) and this approach was chosen as a) many people living with advanced cancer have symptoms of both depression and anxiety ( Cheung et al, 2009 ; Bender et al, 2005 ) b) cancer patient focus groups confirmed this was acceptable ( Karageorge et al, 2017 ) c) transdiagnostic iCBT is effective in community samples ( Newby et al, 2016 ; Pasarelu et al, 2017 ) and cancer survivors ( Murphy et al, 2020 ; Dirkse et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that five of the articles are reviews points to the depth of the extant literature in this rapidly growing area. A number of the studies compared eHealth interventions to face‐to‐face approaches to manage distress, anxiety, depression, and other psychological issues faced by people affected by cancer . Interestingly, numerous studies targeted fear of recurrence, either as a primary or secondary focus .…”
mentioning
confidence: 99%
“…A number of the studies compared eHealth interventions to face‐to‐face approaches to manage distress, anxiety, depression, and other psychological issues faced by people affected by cancer . Interestingly, numerous studies targeted fear of recurrence, either as a primary or secondary focus . Other studies targeted diverse symptoms and treatment side effects, including pain, insomnia, and neurotoxicity .…”
mentioning
confidence: 99%